Comparison of cotton (Gossypium hirsutum) hybrids and their non-transgenic in India - Singh, Kulvir; Mishra, Sudhir Kumar; Singh, Manpreet; Brar, Harjeet Singh; Singh, Amarpreet (Emirates Journal of Food and Agriculture, 2023)
It is still not clear whether differential response of Bt cotton and conventional non-Bt cotton genotypes in terms of growth, phenology and yield ability are hypothetical or realistic. This study investigated the response of three Bt cotton hybrids in comparison to their conventional non-transgenic version (near-isogenic lines) along with two locally adapted genotypes for growth, yield attributes, phenological characteristics and rooting behavior. Therefore, two experiments were conducted during summer season of year 2016 and 2017 to evaluate differences among 3 popular Bt cotton hybrids along with their non-Bt version. First field experiment was conducted as a pot study wherein shoot and root parameters of 3 Bt cotton hybrids (Ankur 3028, MRC 7017, Bioseed 6588) were compared with their non-Bt version along with 2 local checks (i.e.,hirsutum cotton Cv. F2228 and arboreum cottonCv. FDK124). Second field experiment evaluated growth, phenological characteristics, yield attributes and productivity potential of above mentioned Bt and non-Bt hybrids. Findings of pot experiment could not establish any significant difference among studied Bt and non-Bt hybrids for root and shoot characteristics. However, arboreum cotton FDK124 exhibited higher root length than all genotypes. Results of second experiment revealed significant differences for phenological characteristics, wherein Bt version of all the tested hybrids exhibited earliness for flowering initiation, 50 % flowering and days to maturity over their non-Bt version. Seed cotton yield (SCY) in all hybrids possessing Bt gene was significantly higher than their non-Bt version primarily due to higher bolls plant-1. Studies conclude that introgression of Bt gene could not alter rooting parameters of evaluated cotton genotypes but significantly affected phenological stages by inducing earliness and higher SCY in Bt versions due to improved bolls plant-1. Keywords: Bt cotton; Near-isogenic lines; Phenology; Root dry matter; Seed cotton yield